A method for synthesizing low-viscosity polyalphaolefin synthetic oil

By using composite ionic liquid catalysts for polymerization, the loss and corrosion problems of traditional PAO catalysts are solved, and efficient and environmentally friendly low viscosity PAO synthesis is achieved, with high catalytic activity and good product performance.

CN117185888BActive Publication Date: 2025-04-08TIANJIN POLYTECHNIC UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210604719.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-04-08
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing PAO polymerization catalysts have problems with catalyst loss and inactivation, and traditional catalysts such as AlCl3 and BF3 are corrosive to the environment and equipment.

Method used

The composite ionic liquid catalyst is used to synthesize low viscosity PAO through polymerization, and the types and proportions of cations and anions are regulated to achieve accurate synthesis of low viscosity PAO.

Benefits of technology

High catalytic activity, reusable, green and environmentally friendly catalysts are achieved, and the yield and selectivity of PAO are improved. The kinematic viscosity of the product is 6 to 10 cSt, the pour point is less than -50℃, and the flash point reaches more than 230℃.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention provides a method for synthesizing low-viscosity polyalphaolefin synthetic oil, including the following contents: slowly dripping a composite ionic liquid catalyst into a C9-C11 fraction of a stable heavy oil under a nitrogen atmosphere for polymerization reaction, stopping stirring after the reaction is completed, cooling, layering the PAO polymerization product and the composite ionic liquid catalyst, adding a 10wt% NaOH solution to the upper PAO polymerization product and rapidly stirring, separating the liquids, taking the upper oily liquid and distilling it under reduced pressure to obtain the final PAO product, and recycling the composite ionic liquid catalyst of the lower layer. The present invention adopts a composite ionic liquid catalyst, and through polymerization reaction, a directional synthetic low-viscosity PAO product is obtained. The method of the present invention has high selectivity for olefins, high conversion rate of alpha olefins in the raw material, and has broad application prospects in the field of synthesizing low-viscosity polyalphaolefin synthetic oils.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of petrochemical industry, and specifically to a method for producing low-viscosity poly-alpha-olefin synthetic oil by using composite ionic liquid as catalyst. Background Art

[0002] Lubricating oil refers to an oily liquid applied to the surface of the moving parts of a machine, which mainly plays the role of lubrication, cooling, rust prevention, cleaning, sealing and buffering. The base oil of lubricating oil can be divided into mineral base oil and synthetic base oil, among which mineral base oil is the most used. With the development of modern industry and the technological progress of engines and other mechanical equipment, higher and higher requirements are placed on the quality of lubricating oil. However, mineral oil base oil cannot meet the use requirements under certain harsh conditions. At the same time, in some high-precision and cutting-edge technical fields, high-performance lubricating oil is also urgently needed. Synthetic lubricating oil refers to a high-performance lubricating oil blended with a base oil synthesized by chemical polymerization and corresponding oil additives. There are many types of synthetic oils, among which polyalphaolefin synthetic oils have been studied more fully.

[0003] Polyalphaolefin synthetic oil (PAO) is a relatively regular long-chain alkane obtained by polymerization and hydrogenation of alpha olefins under the action of a catalyst. Polyalphaolefin synthetic oil is a kind of oil product with excellent performance. Compared with mineral base oil, it has significant advantages in evaporation loss, pour point, viscosity index and thermal oxidation stability. In addition, its raw material source is wide, the production process is simple, and the price is relatively cheap, so it is widely used and is one of the synthetic lubricant varieties with development potential. The performance of PAO is affected by raw materials, degree of polymerization and molecular weight distribution, and the catalyst is the decisive factor. Therefore, the research on PAO polymerization catalysts is particularly valued. At present, the main PAO polymerization catalysts are Ziegler-Natta catalysts, Lewis acid catalysts, ionic liquid catalysts, etc.

[0004] Lewis acid catalysts are the most commonly used catalyst types in PAO polymerization. The most commonly used Lewis acid catalysts are AlCl 3 and BF 3 Lewis acid catalysts have a wide range of applications, mild reaction conditions, and low requirements for the purity of raw materials. However, Lewis acid catalysts can expose some problems when used. Common AlCl 3 and BF 3 It is highly acidic and will generate highly corrosive acidic HCl and HF gases when it encounters moisture in the air, which will cause serious corrosion to the equipment. Once a leakage accident occurs, it will endanger human health. It will also cause harm to the environment. 3Catalysts can reduce the generation of industrial waste, but there are problems of catalyst loss and deactivation during use. Metallocene catalysts have attracted the attention of many scientific researchers due to their extremely high catalytic activity and excellent single active center characteristics. Olefin polymers prepared by polymerization with metallocene catalysts have excellent performance and high olefin conversion rate. However, the catalyst preparation conditions are harsh and expensive, and the MOA co-catalyst used in the polymerization is expensive and extremely sensitive to water vapor, which greatly increases the production cost and difficulty of production operation. Seeking a catalyst with high catalytic activity, reusability, and green environmental protection is the focus of research by scientists at home and abroad in the century.

[0005] Ionic liquid refers to a liquid composed entirely of ions. Ionic liquids are composed of positive and negative ions. Its most important feature is that it can be designed. It can be regarded as both organic and inorganic substances. By changing the different combinations of cations and anions, different ionic liquids can be designed and synthesized. Compared with other catalysts, ionic liquids have unique chemical properties: high polarity, low viscosity, high liquid temperature range, thermal stability, wide adjustability, incompatibility with specific organic solvents, and no vapor pressure. With the in-depth research, new understandings have been gained on the interaction between anions and cations in ionic liquids, and the concept of Z-bond has been proposed. Z-bond defines a special type of hydrogen bonding between charged ions. The bond energy of Z-bond is significantly higher than that of ordinary hydrogen bonding, reflecting the coupling of electrostatics and hydrogen bonding. Ionic liquids are not only confined to liquids, they can be in the form of liquids, gels, quasi-solids, solids, etc. As catalysts, ionic liquids provide a special chemical microenvironment for chemical reactions that is different from traditional molecular solvents, which can change the reaction mechanism, make the catalyst more active and stable, and improve the conversion rate and selectivity of the catalytic reaction.

[0006] The structure and flow characteristics of synthetic PAO depend on the catalyst system used. 3 and AlCl 3 The catalysts produce low viscosity (2-10 cSt) and high viscosity (40-100 cSt) PAOs, respectively. It is reported that haloaluminate ionic liquids can be considered as catalyst systems for advanced olefin oligomers. Kenneth D Hope et al. used Et 3 NHCl-AlCl 3 Ionic liquid catalysts catalyzed the polymerization of 1-decene to synthesize PAO lubricating oil with a viscosity index of 152 and a pour point of -39°C. Wang Weiwei et al. used 1-decene as raw material and used [Emim]Cl / AlCl 3 Ionic liquid catalyst, when AlCl 3When the molar ratio of [Emim]Cl is 2:1 and the mass fraction of the catalyst is 10%, the kinematic viscosity of the obtained product at 100°C is greater than 10.34 cSt when the reaction temperature is 60°C and the reaction time is 4h. Summary of the invention

[0007] In view of the shortcomings of the prior art, the present invention provides a method for synthesizing low-viscosity polyalphaolefin synthetic oil. The present invention adopts a composite ionic liquid catalyst to synthesize a low-viscosity PAO product in a directional manner through a polymerization reaction. The method of the present invention has high selectivity for olefins and high conversion rate of alpha olefins in the raw materials, and has broad application prospects in the field of synthesizing low-viscosity polyalphaolefin synthetic oil.

[0008] The method for synthesizing low-viscosity polyalphaolefin synthetic oil of the present invention comprises the following contents: slowly dropping a composite ionic liquid catalyst into a C9-C11 fraction of a stable heavy oil in a nitrogen atmosphere to carry out a polymerization reaction, stopping stirring after the reaction is completed, cooling, separating the PAO polymerization product and the composite ionic liquid catalyst into layers, adding a certain concentration of NaOH solution to the upper PAO polymerization product and rapidly stirring, separating the liquids, taking the upper oily liquid and performing reduced pressure distillation to obtain a final PAO product, and recycling the lower composite ionic liquid catalyst for use.

[0009] In the method of the present invention, the composite ionic liquid catalyst comprises cations and anions, wherein the cations comprise at least one of 1-alkyl-3-methyl-imidazolium, and the remaining cations are selected from one or more of N-alkylpyridinium and tetraalkyl quaternary ammonium salts; the alkyl substituent is a normal alkyl group of C2 to C8, such as ethyl, propyl, butyl, pentyl, hexyl, heptyl, and octyl; the anions comprise at least one of aluminum halides, and the remaining anions are selected from one or more of iron, zinc, zirconium, copper, and tin halides, and the halides may be chlorides or bromides.

[0010] In the method of the present invention, the molar ratio of the 1-alkyl-3-methylimidazolium salt to the remaining cations is 5:1 to 1:5.

[0011] In the method of the present invention, the molar ratio of the aluminum halide to other metal halides is 3:1 to 20:1.

[0012] In the method of the present invention, the composite ionic liquid catalyst can be purchased as a commercial product, or the desired ionic liquid can be designed and synthesized by the prior art in the art.

[0013] In the method of the present invention, the C9-C11 fraction of the stable heavy oil includes 1-nonene, 1-decene, 1-undecene and part of C9-C11 alkanes.

[0014] In the method of the present invention, the composite ionic liquid catalyst accounts for 5wt% to 10wt% of the alpha olefins in the C9-C11 fraction of the stable heavy oil by mass.

[0015] In the method of the present invention, the polymerization reaction temperature is 80 to 170° C., preferably 120 to 170° C., and the polymerization reaction time is 10 to 40 minutes.

[0016] In the method of the present invention, the mass percentage concentration of the NaOH solution is 5 to 20 wt%, preferably 8 to 10 wt%.

[0017] Compared with the prior art, the method of the present invention has the following advantages: the composite ionic liquid catalyst described in the method of the present invention has good catalytic activity, and has a high yield and selectivity for olefin polymerization. The composite ionic liquid catalyst provides a special chemical microenvironment, which allows olefins to be better dissolved in the ionic liquid, which is beneficial to improving the selectivity and yield of polymerization. Experimental data show that the yield of the composite ionic liquid catalyst described in the method of the present invention can reach more than 88%, the kinematic viscosity of the synthesized PAO is 6 to 10 cSt at 100°C, the pour point is less than -50°C, and the flash point can reach more than 230°C. The results of high-temperature simulation analysis and determination show that the synthesized low-viscosity PAO is mainly composed of trimers and tetramers. The present invention can achieve precise synthesis of low-viscosity PAO by regulating the types and proportions of cations and anions in the composite ionic liquid catalyst.

[0018] At the same time, the preparation method of the composite ionic liquid catalyst of the present invention is simple, the raw materials are simple and easy to obtain, the separation operation of the catalyst and the PAO product is simple, and the recovered composite ionic liquid catalyst still has good catalytic activity. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0020] The composite ionic liquid catalyst according to the present invention can be prepared by the following method:

[0021] 1-Alkyl-3-methylimidazolium salt: 1-methylimidazole and halogenated normal alkane are stirred evenly at a molar ratio of 1:1.2 under a pressure of 0.1-0.2 MPa, heated to 110°C, and reacted for 3 days. A white solid is obtained by filtration, washed three times with ethyl acetate, and dried.

[0022] N-Alkylpyridinium salt: Pyridine and halogenated normal alkane are stirred evenly at a molar ratio of 1:1.4 under a pressure of 0.1-0.3 MPa, heated to 130°C, and reacted for 4 days. The white solid is filtered, washed three times with ethyl acetate, and dried.

[0023] Tetraalkyl quaternary ammonium salt: alkyl-containing amine halide and halogenated normal alkane are stirred evenly at a molar ratio of 1:1.2 under a pressure of 0.1-0.2 MPa, heated to 110°C, and reacted for 3 days. The white solid is filtered, washed three times with ethyl acetate, and dried.

[0024] A tetraalkyl quaternary ammonium salt, a 1-alkyl-3-methylimidazolium salt and an N-alkylpyridinium salt are stirred with a metal halide (one or more of halides of aluminum, iron, zinc, zirconium, copper and tin) in an anhydrous and oxygen-free environment to obtain an ionic liquid catalyst. The anhydrous and oxygen-free environment can be achieved by operating the above steps in a glove box or by using a double row of tubes. Then, by regulating the types and ratios of cations and anions, the composite ionic liquid catalyst required in the present application is obtained.

[0025] The low viscosity PAO test involved in the present invention adopts the following method

[0026] Testing of kinematic viscosity and viscosity index

[0027] The kinematic viscosity and viscosity index were tested according to the GB / T29617 method, and the kinematic viscosity and viscosity index of the oil at 40°C and 100°C were measured using a fully automatic kinematic viscometer (SVM3001, Anton Paar). Turn on the power switch to enter the work project interface, set the parameters, place the oil sample to be tested on the automatic sample rack, and start the test.

[0028] Pour point test

[0029] The pour point test method refers to the national standard GB / T3535-2006 method. Place the oil sample in a pour point test tube, then place the pour point test tube with the oil sample in a pour point tester (BY-12). Every time the temperature drops by 3°C, take out the pour point test tube and tilt it 45 degrees to observe whether the oil flows. If it flows, continue to cool down. When the oil stops flowing after tilting, record the temperature at this time and add 3°C to get the pour point of the sample to be tested.

[0030] Open-cup flash point test

[0031] The test of open flash point refers to the GB / T3536 method. The sample is placed in the test cup, and the test cup containing the test oil is heated. The lowest temperature of the condensed synthetic gas formed by the generated oil vapor and the surrounding air when the flame contacts and flashes is taken as the flash point. The computer sends instructions from the I / O port according to the collected temperature changes to control the heater so that the temperature of the test oil rises at a certain rate. The scanning cycle, ignition time, differential detection, etc. are all automatically controlled. When the flash is detected, the computer system stops data collection, displays the flash temperature and prints the record results, stops heating, turns off the flame, and the arm automatically rises, and the experiment ends.

[0032] Synthesis of ionic liquids

[0033] Example 1

[0034] 1-Methylimidazole and 1-chlorobutane were mixed in a molar ratio of 1:1.2, and then added to a high-pressure reactor. Nitrogen was filled to make the pressure in the reactor reach 0.2MPa. The reactor was heated to 110°C under continuous stirring for 3 days. The obtained white solid was washed with ethyl acetate several times, and the white solid obtained after drying was 1-butyl-3-methylimidazole chloride. 1-Butyl-3-methylimidazole chloride was mixed with aluminum chloride in a molar ratio of 1:2, and stirred for 2 hours at room temperature without water and oxygen to form an ionic liquid. This is the basic ionic liquid 1-butyl-3-methylimidazole aluminum tetrachloride used for compounding composite ionic liquids. Collect in a dryer for use.

[0035] Example 2

[0036] Pyridine and 1-chlorobutane were mixed in a molar ratio of 1:1.3, and then added to a high-pressure reactor. Nitrogen was filled to make the pressure in the reactor reach 0.3MPa. The reactor was heated at 130°C under continuous stirring for 7 days. The obtained white solid was washed with ethyl acetate several times, and the white solid obtained after drying was 1-butylpyridine chloride. 1-Butylpyridine chloride was mixed with aluminum chloride in a molar ratio of 1:2, and stirred for 2 hours at room temperature without water and oxygen to form an ionic liquid. This is the basic ionic liquid 1-butylpyridine chloride aluminum tetrachloride salt used for compounding composite ionic liquids. Collect in a dryer for use.

[0037] Example 3

[0038] Triethylamine and 1-chlorobutane were mixed in a molar ratio of 1:1.3, and then added to a high-pressure reactor. Nitrogen was filled to make the pressure in the reactor reach 0.3MPa. The reaction was continued at 130°C under continuous stirring for 7 days. The obtained white solid was washed with ethyl acetate several times, and the white solid obtained after drying was triethylbutylammonium chloride. Triethylbutylammonium chloride was mixed with aluminum chloride in a molar ratio of 1:2, and stirred for 2 hours at room temperature without water and oxygen to form an ionic liquid. This is triethylbutylammonium chloride, the basic ionic liquid used to prepare composite ionic liquids. Collect in a dryer for later use.

[0039] Example 4

[0040] Add metal compounds CuCl, AlCl to the ionic liquid in Example 1 3 The molar ratio of 1-butyl-3-methylimidazole / AlCl was 3:1, and the mixture was stirred for 4 hours until all the solid substances added were dissolved. 3 / CuCl).

[0041] Example 5

[0042] Add the metal compound ZrCl to the ionic liquid in Example 1 4 , AlCl 3 With ZrCl 4 The molar ratio of 1-butyl-3-methylimidazole / AlCl 3 / ZrCl 4 ).

[0043] Example 6

[0044] The ionic liquid in Example 1 and the ionic liquid in Example 2 were mixed in a molar ratio of 1:1, and AlCl 3 , the molar ratio of the total amount of the ionic liquids in Example 1 and Example 2 to the anions is controlled to be 1:2, until all the added solid substances are dissolved. That is, the composite ionic liquid (1-butyl-3-methylimidazole / 1-butylpyridine / AlCl 3 ).

[0045] Example 7

[0046] The ionic liquid in Example 1, the ionic liquid in Example 3 and AlCl 3 The mixture was mixed evenly in a molar ratio of 2:1:6 and stirred in a glove box for 4 h until all the added solid substances were dissolved. The composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / AlCl 3 ).

[0047] Example 8

[0048] In the ionic liquid of Example 7, a second metal compound CuCl is introduced to control the AlCl 3 The molar ratio of CuCl to 1 was 5:1, and the mixture was stirred in a glove box for 4 h until all the solid substances added were dissolved. 3 / CuCl).

[0049] Example 9

[0050] The ionic liquids of Example 1 and Example 3 and commercially available ethylamine hydrochloride were mixed with AlCl 3 The four were mixed evenly in a molar ratio of 1:1:1:6 and stirred in a glove box for 4 hours until all the added solid substances were dissolved. The composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / ethylamine hydrochloride / AlCl 3 ).

[0051] Example 10

[0052] The second metal compound CuCl was introduced into the ionic liquid in Example 9 to control the AlCl 3 The molar ratio of CuCl to 1 was 5:1, and the mixture was stirred in a glove box for 4 h until all the solid substances added were dissolved. The composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / ethylamine hydrochloride / AlCl 3 / CuCl).

[0053] Preparation of low viscosity PAO

[0054] Embodiment 11

[0055] In a dehydrated and deoxygenated four-necked flask filled with nitrogen, a composite ionic liquid (1-butyl-3-methylimidazole / AlCl 3 / CuCl) is sealed and stirred. The amount of catalyst is 8wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 140°C, and the reaction is continued for 20 minutes after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. It is known from the test that the yield of PAO is 91%, the viscosity at 100°C is 6.96cSt, the viscosity index is 130.5, the pour point is -52°C, and the flash point is 235°C.

[0056] Example 12

[0057] In a dehydrated and deoxygenated four-necked flask filled with nitrogen, a composite ionic liquid (1-butyl-3-methylimidazole / AlCl 3 / ZrCl 4 ) is sealed and stirred. The amount of catalyst is 7wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 120°C, and the reaction is continued for 20 minutes after the raw material is added. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. According to the test, the yield of PAO is 88%, the viscosity at 100°C is 7.03cSt, the viscosity index is 131.42, the pour point is -51oC, and the flash point is 232°C.

[0058] Embodiment 13

[0059] In a dehydrated and deoxygenated four-necked flask filled with nitrogen, a composite ionic liquid (1-butyl-3-methylimidazole / 1-butylpyridine / AlCl 3 ) is sealed and stirred. The amount of catalyst is 9wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 130°C, and the reaction is continued for 20 minutes after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. According to the test, the yield of PAO is 96%, the viscosity at 100°C is 10.04cSt, the viscosity index is 137.69, the pour point is -56°C, and the flash point is 237°C.

[0060] Embodiment 14

[0061] In a dehydrated and deoxygenated four-necked flask filled with nitrogen, a composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / AlCl 3) is sealed and stirred. The amount of catalyst is 9wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 150°C, and the reaction is continued for 20 minutes after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. According to the test, the yield of PAO is 88%, the viscosity at 100°C is 7.98cSt, the viscosity index is 132.72, the pour point is -51°C, and the flash point is 232°C.

[0062] Embodiment 15

[0063] In a dehydrated and deoxygenated four-necked flask filled with nitrogen, a composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / AlCl 3 / CuCl)) is sealed and stirred. The amount of catalyst is 8wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 150°C, and the reaction is continued for 30min after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. It is known from the test that the yield of PAO is 90%, the viscosity at 100°C is 6.04cSt, the viscosity index is 130.4, the pour point is -52°C, and the flash point is 233°C.

[0064] Example 16

[0065] In a dehydrated and deoxygenated nitrogen-filled four-necked flask, a composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / ethylamine hydrochloride / AlCl 3 ) is sealed and stirred. The amount of catalyst is 7wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 130°C, and the reaction is continued for 30 minutes after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. According to the test, the yield of PAO is 93%, the viscosity at 100°C is 9.02cSt, the viscosity index is 130.5, the pour point is -54°C, and the flash point is 232°C.

[0066] Embodiment 17

[0067] In a dehydrated and deoxygenated nitrogen-filled four-necked flask, a composite ionic liquid (1-butyl-3-methylimidazole / triethylbutylammonium chloride / ethylamine hydrochloride / AlCl 3 / CuCl)) is sealed and stirred. The amount of catalyst is 8wt% (calculated based on the alpha olefin content in the raw material), 120g of the C9-C11 fraction of the stable heavy oil is slowly added dropwise and continued to stir to cause polymerization reaction, the reaction temperature is controlled to be 160°C, and the reaction is continued for 30 minutes after the raw material is added dropwise. After the reaction is completed, the catalyst and the PAO polymerization product are separated. Take the PAO polymerization product, add 30mL of 10wt% NaOH solution, stir and stand, wash and separate the liquids with water for many times, and then distill under reduced pressure to obtain the final PAO product. It is known from the test that the yield of PAO is 92%, the viscosity at 100°C is 5.83cSt, the viscosity index is 130.1, the pour point is -53°C, and the flash point is 235°C.

Claims

1. A method for synthesizing low-viscosity polyalphaolefin synthetic oil, characterized in that include: The composite ionic liquid catalyst is slowly added dropwise to the C9-C11 fraction of the stable heavy oil under nitrogen atmosphere to carry out polymerization reaction. After the reaction is completed, stirring is stopped and the reaction is cooled. The PAO polymerization product and the composite ionic liquid catalyst are separated into layers. A certain concentration of NaOH solution is added to the upper layer of the PAO polymerization product and the mixture is stirred rapidly. The liquid is separated and the upper layer of the oily liquid is distilled under reduced pressure to obtain the final PAO product. The PAO product is a low-viscosity poly-alpha olefin synthetic oil. The composite ionic liquid catalyst in the lower layer is recycled and used. The composite ionic liquid catalyst comprises cations and anions, wherein the cations comprise at least one of 1-alkyl-3-methyl-imidazolium and the remaining cations, and the remaining cations are selected from one or more of N-alkylpyridinium and tetraalkyl quaternary ammonium salts; the alkyl in the 1-alkyl-3-methyl-imidazolium is a normal alkyl of C2 to C8; the anions comprise at least one of aluminum halides and the remaining anions, and the remaining anions are selected from one or more of iron, zinc, zirconium, copper and tin halides, and the halide is chloride or bromide.

2. The method according to claim 1, characterized in that: The molar ratio of the 1-alkyl-3-methylimidazolium salt to the remaining cations is 5:1 to 1:

5.

3. The method according to claim 1, characterized in that: The molar ratio of the aluminum halide to the remaining anions is 3:1 to 20:

1.

4. The method according to claim 1, characterized in that: The C9-C11 fraction of the stable heavy oil includes 1-nonene, 1-decene, 1-undecene and part of C9-C11 alkanes.

5. The method according to claim 1, characterized in that: The composite ionic liquid catalyst accounts for 5wt% to 10wt% of the alpha olefins in the C9-C11 fraction of the stable heavy oil by mass.

6. The method according to claim 1, characterized in that: The polymerization reaction temperature is 80-170° C., and the polymerization reaction time is 10-40 minutes.

7. The method according to claim 1, characterized in that: The mass percentage concentration of the NaOH solution is 5-20wt%.

8. The method according to claim 1, characterized in that: The low-viscosity poly-alpha-olefin synthetic oil has a kinematic viscosity of 6 to 10 cSt at 100° C., a pour point of less than -50° C., and a flash point of more than 230° C.

9. Use of a composite ionic liquid catalyst in synthesizing a low-viscosity poly-alpha-olefin synthetic oil as claimed in any one of claims 1 to 8, characterized in that: The composite ionic liquid catalyst comprises cations and anions, wherein the cations comprise at least one of 1-alkyl-3-methyl-imidazolium and the remaining cations, and the remaining cations are selected from one or more of N-alkylpyridinium and tetraalkyl quaternary ammonium salts; the anions comprise at least one of aluminum halides and the remaining anions, and the remaining anions are selected from one or more of halides of iron, zinc, zirconium, copper and tin.

10. The use according to claim 9, characterized in that: The molar ratio of the 1-alkyl-3-methylimidazolium salt to the remaining cations is 5:1 to 1:5; the molar ratio of the aluminum halide to the remaining anions is 3:1 to 20:1.

Citation Information

Patent Citations

  • Manufacture of oligomers from nonene

    CN102648219A

  • Process for making a high viscosity base oil with an improved viscosity index

    CN103210071A